Population Dynamics and Dispersion of Frankliniella schultzei (Trybom) (Thysanoptera: Thripidae) on Lettuce under Hydroponic Cultivation in Greenhouse - Submok , Rattigan; Uraichuen, Sopon (Agriculture and Natural Resources, 2015)
Studies were conducted on the population dynamics of Frankliniella schultzei (Trybom) on Iceberg, Red Salad Bowl and Red Rapid lettuce cultivars grown hydroponically at Pathum Thani province, Thailand. In addition, studies were carried out on the dispersion patterns of F. schultzei on hydroponically grown Green Oak Leaf, Red Oak Leaf and Butterhead in Nakhon Pathom province, Thailand. The population of F. schultzei was not detectable in January and February 2012. However, the population clearly increased to its peak in the March planting and then sharply declined in the April planting. The temperature and the relative humidity did not have any effect on the population dynamics of F. schultzei. The dispersion of F. schultzei on the upper side and lower side of lettuce leaves was found to be most abundant at Sampling Point 3 on the upper side of the leaves of all three lettuce cultivars. On the lower side of the leaves of the three cultivars of lettuce, it was most abundant at Sampling Point 5 on Green Oak Leaf and Red Oak Leaf and at Sampling Point 3 on Butterhead only. The populations of F. schultzei, showed a uniform dispersion pattern on Green Oak Leaf and Red Oak Leaf and a clumped dispersion pattern on Butterhead.